UPAYA MENINGKATKAN HASIL BELAJAR BOLA VOLI MELALUI MODIFIKASI BOLA VOLI MINI PADA SISWA KELAS VI SDN 3 SELAT HULU TAHUN PELAJARAN 2020/2021 - Tri Astuti (JURNAL ILMIAH EDUNOMIKA, 2022)
Learning Physical Education, Sports and Health which is often not in accordance with the characteristics of students makes children's creativity to be neglected and learning outcomes are less than optimal. So it is necessary to modify the actual learning media. The problem and this research is "Can learning using modifications of mini volleyball improve volleyball learning outcomes in class VI SDN 3 Selat Hulu District, Selat District, Kapuas Regency?" The purpose of this study was to determine the improvement of volleyball learning outcomes through modification of mini volleyball. This research was conducted at SD 3 Selat Hulu Kapuas Regency, the sample in this study was class VI students, totaling 20 students. This research is a classroom action research consisting of two cycles where each cycle consists of 4 stages, namely planning, action, observation (observation), and reflection. Data collection techniques in this study used observation sheets and questionnaires used to determine student understanding. on volleyball. The data from the observations of cycles I and II, namely: performance (psychomotor) obtained results of 40% and 85% with good criteria. The data from the observation of attitudes and behavior (affective) were 20% and 90% with good criteria. The data on the results of the assessment of student understanding (cognitive) were 45% and 95% with very good criteria. Based on the comparison of the results achieved between cycle I and cycle II, the overall value obtained for each aspect has increased. Based on the results of the research above, it is concluded that learning by using modified mini volleyball can improve student volleyball learning outcomes. Therefore, it is expected that students with modifications to the mini volleyball game will be more enthusiastic about participating in PJOK learning, for PJOK teachers at SDN 3 Selat Hulu can use modifications of mini volleyball in volleyball lessons, use modifications of mini volleyball games as an alternative to learning PJOK , schools are also expected to improve existing facilities and infrastructure as a support in PJOK learning.